2015
DOI: 10.1016/j.jhep.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine increases circulating very-low density lipoprotein clearance in non-alcoholic fatty liver disease

Abstract: Background Very-low density-lipoproteins (VLDL) export lipids from liver to peripheral tissues and are the precursors of low-density-lipoproteins. Low levels of hepatic S-adenosylmethionine (SAMe) decrease triglyceride (TG) secretion in VLDL contributing to hepatosteatosis in methionine adenosyltransferase 1A knockout mice but nothing is known about the effect of SAMe over circulating VLDL metabolism. Objective We wanted to investigate whether excess SAMe could disrupt VLDL plasma metabolism and unravel the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 47 publications
3
29
0
4
Order By: Relevance
“…We have previously shown that feeding Gnmt -KO mice during 21 days with a methionine deficient diet (MDD) restored normal SAMe levels[17], recovered VLDL metabolism[36], decreased liver TG content, and ameliorated liver steatosis[17]. …”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that feeding Gnmt -KO mice during 21 days with a methionine deficient diet (MDD) restored normal SAMe levels[17], recovered VLDL metabolism[36], decreased liver TG content, and ameliorated liver steatosis[17]. …”
Section: Resultsmentioning
confidence: 99%
“…In our study, HBc not only regulated glycine metabolites expression but also directly affected the activity by binding with enzymes in the glycine metabolic pathway. Previous studies have found that these enzymes might be promising biomarker candidates for HCC31 and non-alcoholic fatty liver disease32. However, whether these enzymes play important roles in HBV-related HCC requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…More specifically, glycine is utilized to catabolize excess S-adenosylmethionine by its remethylation into sarcosine via the enzyme glycine-N-methyltransferase (GNMT), 10 and excess hepatic S-adenosylmethionine concentrations have been linked to the regulation of apolipoprotein (apo) B mRNA expression and very low-density lipoprotein formation. [11][12][13] Disturbances in these reactions have been associated with lipid accumulation both in the liver and in macrophages, which further promotes oxidized low-density lipoprotein (LDL)-induced foam cell formation in the artery wall. 12 Therefore, glycine availability may affect lipid metabolism and thereby further modulate the risk of coronary artery disease (CAD).…”
mentioning
confidence: 99%